2020
DOI: 10.1016/j.bbagrm.2019.194431
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of regulatory knowledge from human to mouse for functional genomics analysis

Abstract: Transcriptome profiling followed by differential gene expression analysis often leads to unclear lists of genes which are hard to analyse and interpret. Functional genomic tools are powerful approaches for downstream analysis, as they summarize the large and noisy gene expression space in a smaller number of biological meaningful features. In particular, methods that estimate the activity of processes by mapping transcripts level to process members are popular. However, footprints of either a pathway or transc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
134
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 121 publications
(137 citation statements)
references
References 28 publications
3
134
0
Order By: Relevance
“…However, both PROGENy and GO-GSEA performed poorly for some pathways, e.g., WNT pathway. We reason that this observation might be due to the quality of the corresponding benchmark data [33]. Given this fact and that GO-GSEA cannot handle low gene coverage (in our hands), we concluded that this approach is not suitable for scRNA-seq analysis.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, both PROGENy and GO-GSEA performed poorly for some pathways, e.g., WNT pathway. We reason that this observation might be due to the quality of the corresponding benchmark data [33]. Given this fact and that GO-GSEA cannot handle low gene coverage (in our hands), we concluded that this approach is not suitable for scRNA-seq analysis.…”
Section: Discussionmentioning
confidence: 84%
“…PROGENy is a tool that infers pathway activity for 14 signaling pathways (Androgen, Estrogen, EGFR, Hypoxia, JAK-STAT, MAPK, NFkB, PI3K, p53, TGFb, TNFa, Trail, VEGF, and WNT) from gene expression data [12,33]. By default pathway activity inference is based on gene sets comprising the top 100 most responsive genes upon corresponding pathway perturbation, which we refer to as footprint genes of a pathway.…”
Section: Functional Analysis Tools Gene Set Resources and Statisticmentioning
confidence: 99%
“…5d). Using the TF-target gene database, DoRothEA, we identified expressed TFs known to regulate these genes [26, 27]. Five genes had no known and expressed regulator, thus were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Pathway analysis with PROGENy. Pathway activity scores were calculated with the functional genomics tools PROGENy [26,27]. While classical pathway analysis methods (e.g., Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis) rely on gene sets containing genes of pathway members PROGENy exploits so called "footprint gene sets" containing not the pathway members but the most responsive genes upon corresponding pathway perturbation.…”
Section: Functional Genomics Analysis Of the CCL 4 Signaturementioning
confidence: 99%
“…Transcription factor (TF) analysis with DoRothEA. DoRothEA is a high-quality data resource of TF-target interactions (regulons) [26,28]. Coupling DoRothEA regulons with a statistical method allows to infer TF activity from the expression of its transcriptional targets.…”
Section: Functional Genomics Analysis Of the CCL 4 Signaturementioning
confidence: 99%